Controllability of nonlinear stochastic neutral fractional dynamical systems - Rajendran, Mabel Lizzy Lizzy; Balachandran, Krishnan; Trujillo, Juan J. J. (Nonlinear Analysis: Modelling and Control, 2017)
In this paper, we obtain an equivalent nonlinear integral equation to the stochastic neutral fractional system with bounded operator. Using the integral equation, the sufficient conditions for ensuring the complete controllability of the stochastic fractional neutral systems with Wiener and Lévy noise are obtained. Banach’s fixed point theorem is used to obtain the results. Examples are provided to illustrate the theory.